2007
DOI: 10.1016/j.ccr.2007.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Loss of β-Catenin Impairs the Renewal of Normal and CML Stem Cells In Vivo

Abstract: A key characteristic of stem cells and cancer cells is their ability to self-renew. To test if Wnt signaling can regulate the self-renewal of both stem cells and cancer cells in the hematopoietic system, we developed mice that lack beta-catenin in their hematopoietic cells. Here we show that beta-catenin-deficient mice can form HSCs, but that these cells are deficient in long-term growth and maintenance. Moreover, beta-catenin deletion causes a profound reduction in the ability of mice to develop BCR-ABL-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
525
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(546 citation statements)
references
References 61 publications
17
525
1
3
Order By: Relevance
“…Stabilized β-catenin expression expands the pool of HSCs and leads to deficiency in HSCs repopulation capacity [12,13]. Conversely, deletion of β-catenin or Wnt3a leads to defective HSCs long-term maintenance [14,15]. Nevertheless, several lines of evidence also indicate that β-catenin is dispensable for HSCs maintenance [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…Stabilized β-catenin expression expands the pool of HSCs and leads to deficiency in HSCs repopulation capacity [12,13]. Conversely, deletion of β-catenin or Wnt3a leads to defective HSCs long-term maintenance [14,15]. Nevertheless, several lines of evidence also indicate that β-catenin is dispensable for HSCs maintenance [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…86,87 These latter studies have identified different genes (B catenin, Shh, Pml, Alox5 and Foxo) that are essential for CML propagation in recipients. [88][89][90][91][92][93] The challenge now with all of these findings is to determine the extent to which they are relevant to primary CML in humans and to which they can be exploited to design better prognostic or therapeutic approaches. Related to the poor maintenance (that is, rapid loss) of primary human CML stem cells in vitro and difficulties encountered in demonstrating their expansion in vivo, is the growing recognition that these cells are becoming decreasingly available to investigators.…”
Section: Spotlightmentioning
confidence: 99%
“…24 In addition, the K562/HA cell line contained more cells with the side population marker for cancer stem cells (Figure 4g). 25 These findings suggest that the adaptation to hypoxia induces putative stem/ progenitor cell-like characteristics in Bcr-Abl þ cells.…”
mentioning
confidence: 99%